A new technique in evaluation of stabilisation for the design of amorphous silicon photovoltaic modules in grid connected system under equatorial climate / Mohamad Zhafran Hussin - Hussin, Mohamad Zhafran (Institute of Graduate Studies, UiTM, 2014)
The use of thin-film photovoltaic (TFPV) technology is becoming more important with the increasing demands on PV installations in the full humid equatorial climate (Af) country such as Malaysia. There is a lack of literature on performance characterization of the grid-connected photovoltaic (GCPV) systems as well as a method in identifying the instability behaviour in TFPV technology, especially in this region. In this study, research on amorphous-Silicon (a-Si) based singlejunction (SJ) TFPV technology was undertaken to find out the environmental suitability of the GC systems in Af climate. Three objectives have been identified: influence of Af climate on a-Si SJ TFPV technology on system performance, method of assessing the stabilization stages due to light-induced degradation (LID) phenomenon, designing on TFPV derating factor in matching of an Inverter-to-Array Power (IAP) ratio.